2020
DOI: 10.36560/1342020995
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cultivar and pruning management on the phenological aspects of blackberry

Abstract: Among other factors, climate and management may also affect the development and behavior of blackberry, providing different results on cultivars. Therefore the objective of this work was to evaluate the phenological performance of blackberry cultivars and plants conducted with different numbers of primocane. Two experiments were carried out, the first one consisted of the evaluation of four blackberry cultivars: BRS Tupy, Cherokee, BRS Xavante and Guarani, for the second experiment, with the cultivar BRS Tupy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…It is important to note that for all treatments, the SS values obtained were above that reported by Lugaresi et al (2020) and Guedes et al (2013) who found values around 8 °Brix, for cv. Xavante, thus conferring a sweeter taste to the fruits obtained in this work, due to the low overall production.…”
Section: /6supporting
confidence: 54%
See 1 more Smart Citation
“…It is important to note that for all treatments, the SS values obtained were above that reported by Lugaresi et al (2020) and Guedes et al (2013) who found values around 8 °Brix, for cv. Xavante, thus conferring a sweeter taste to the fruits obtained in this work, due to the low overall production.…”
Section: /6supporting
confidence: 54%
“…The blackberry 'Xavante' is very productive, its stems are vigorous and erect, and it does not require much cold to exit dormancy, about 200 to 300 hours of cold (Brugnara, 2016). Flowering starts in September and may extend until January in the southern hemisphere, and its maturation occurs early, starting the harvest in mid-November and extending until mid-March, depending on the climatic conditions of the year (Lugaresi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%